2018
DOI: 10.1016/j.stemcr.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

COPS2 Antagonizes OCT4 to Accelerate the G2/M Transition of Mouse Embryonic Stem Cells

Abstract: SummaryProper regulation of the cell cycle is essential to safeguard the genomic integrity of embryonic stem cells (ESCs) while maintaining the fast proliferation rate. The pluripotency factor OCT4 has been shown to inhibit CDK1 activation, thus preventing mitotic entry and facilitating the maintenance of genomic integrity. Yet, how ESCs enter mitosis in the presence of OCT4 remains unclear. We previously reported that COPS2 promotes the progression through the G2/M phase of mouse ESCs. In this study, through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…Thus, it is uncertain whether the level of cyclin B is upregulated/downregulated in G2/M phase-arrested cells. However, several studies showed that the downregulation of CDK1/cyclin B complex/activity is associated with cell cycle arrest at G2/M phase (24)(25)(26). Consistent with these studies, bufotalin decreased the level of CDK1, which could downregulate the level of CDK1/cyclin B complex, leading to cell cycle arrest at G2/M phase in bufotalin-treated A375 cells in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it is uncertain whether the level of cyclin B is upregulated/downregulated in G2/M phase-arrested cells. However, several studies showed that the downregulation of CDK1/cyclin B complex/activity is associated with cell cycle arrest at G2/M phase (24)(25)(26). Consistent with these studies, bufotalin decreased the level of CDK1, which could downregulate the level of CDK1/cyclin B complex, leading to cell cycle arrest at G2/M phase in bufotalin-treated A375 cells in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…A whole-genome RNA interference screening revealed that COPS1, COPS2, and COPS4 are required for maintaining the expression of the OCT4-GFP reporter in human ESCs, implicating a role of the CSN in pluripotency maintenance (23). However, by knocking down individual CSN subunits, we found that only Cops2, but not any other CSN subunits, is essential for the self-renewal and G2/M transition of mouse ESCs (24,25). Moreover, Cops5 and Cops8 null embryos die after embryonic day 7.5, while no Cops2 null mice survive to embryonic day 7.5 (26)(27)(28).…”
Section: Significancementioning
confidence: 72%
“…Cops5 Regulates Cellular Metabolism through Mtch2. To understand the molecular mechanism of Cops5 in regulating cellular metabolism, we looked into the list of Cops5-interacting proteins identified by coimmunoprecipitation (co-IP) and mass spectrometric analysis (25). We focused on the 49 proteins interacting with Cops5, but not with Cops2 (Dataset S1), because the regulation of cellular metabolism by Cops5 is independent of the CSN.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, we cannot rule out binding of miR-26b-5p to other parts of the transcripts lacking the canonical seed sequences. COPS2 and NOL12 were shown to accelerate cell cycle and promote cell proliferation in several types of tumors [44][45][46]. MRPL15 is a member of human mitochondrial ribosomal proteins (MRPs), which provide energy in the form of ATP for cell growth [47].…”
Section: Discussionmentioning
confidence: 99%